Commercial Vegetable Production: Snap Beans - Marr, Charles W.; Lamont, WM. J.; Tisserat, Ned (My University, 1995)
This publication describes the commercial production of snap beans.
MF2076_1995_02
Keywords: MF2076; Lawn and Garden; fruits and vegetables; equipment and structures; MF